A SURVEY OF EXPLORATORY SEARCH SYSTEMS BASED ON LOD RESOURCES - Jacksi, Karwan; Dimililer, Nazife; Zeebaree, Subhi R. M. (Univ Utara Malaysia-Uum, 2015)
The fact that the existing Web allows people to effortlessly share data over the Internet has resulted in the accumulation of vast amounts of information available on the Web. Therefore, a powerful search technology that will allow retrieval of relevant information is one of the main requirements for the success of the Web which is complicated further due to use of many different formats for storing information. Semantic Web technology plays a major role in resolving this problem by permitting the search engines to retrieve meaningful information. Exploratory search system, a special information seeking and exploration approach, supports users who are unfamiliar with a topic or whose search goals are vague and unfocused to learn and investigate a topic through a set of activities. In order to achieve exploratory search goals Linked Open Data (LOD) can be used to help search systems in retrieving related data, so the investigation task runs smoothly. This paper provides an overview of the Semantic Web Technology, Linked Data and search strategies, followed by a survey of the state of the art Exploratory Search Systems based on LOD. Finally the systems are compared in various aspects such as algorithms, result rankings and explanations.
5th International Conference on Computing & Informatics -- AUG 11-13, 2015 -- Istanbul, TURKEY
Keywords: semantic web; linked data; exploratory search system